ANALISIS BUTIR SOAL PENILAIAN MATA PELAJARAN EKONOMI DALAM KAITANNYA DENGAN ASPEK KOGNITIF TAXONOMY BLOOM - Wahyu Nugraha; Harini Harini; Sudarno Sudarno (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2017)
This research aims to identify the quality of items about the assessment of subjects Economics class XI in SMA Negeri 4 Surakarta in the academic year  2016/2017 in relation to cognitive aspects Taxonomy Bloom. The subjects chosen are Economics subject teachers and students of XI IPS class in SMA Negeri 4 Surakarta academic year 2016/2017, the subject taking technique in this study using the posposive sampling. Meanwhile, the technique used in sampling the data source is by using snowball sampling technique. This research is a descriptive research with qualitative approach. Data collection was obtained by observation method for test development activity data, interview method for test development data and quality of item and documentation for data item quality. The results showed that: (1) a valid question a total of 11 items (36.7%) while invalid 19 items (63.3%). (2) Based on the reliability, including the matter of which the reliability is very low, -0.057. (3) Based on the level of difficulty, including difficult level items totaled 25 questions (83%), moderate level 2 questions (7%), and an easy level 3 questions (10%). (4) Based on the distinguishing features, items that includes not very good 5 questions (16.7%), there is a good 5 questions (16.7%), 10 items are good enough (33.3%), 8 points are good (26, 7%), and splendidly questions are 2 points (6.67%). (5) Based on the effectiveness of the use of distractors, items which serve very good 3 point (10%), serves as good 8 points (26.7%), and 10 items as enough (33.3%), less 5 questions (16.7%), and serves no good / bad 4 items (13.3%). (5) Based on the analysis validity, level of difficulty, distinguishing, and the effectiveness of the use of distractors there are good-quality questions amount to 2 questions (6.7%), unfavorable 6 matter (20%), and not good or bad 22 questions (73.3%). Based on the cognitive aspects of Taxonomy Bloom, the majority of items are dominated by items with category C1 consisting of 13 items (43.3%), category C2 amounted to 11 items (36.7%), category C3 amounted to 3 items (10%) and the items with category C4 amounted to 3 items (10%). Overall matter of assessment of subjectsEconomics class XI SMA Negeri 4 Surakarta Academic year 2016/2017 in relation to the cognitive aspects of Taxonomy Bloom including the problem that is not good.